The Effect Of Motivation And Job Satisfaction On Organizational Citizenship Behavior - Lenie Febriyani; Malik Rismanto (Al-Makki Publisher, 2023)
This research is aimed to determine the influence of: motivation toward organizational citizenship behavior; job satisfaction toward organizational citizenship behavior, and both at once toward the organizational citizenship behavior of employees of the PT Jasa Marga (Persero) Tbk. Palikanci Cirebon Branch Office. The method used in this research is associative. The technique of collecting data is by field research, litelature study and analysis of data. This study uses primary data by distributing questionnaires to 60 employees on PT Jasa Marga (Persero) Tbk. Palikanci Cirebon Branch Office. In this research, motivation has a significant influence toward organizational citizenship behavior. Job satidfaction motivation has a significant influence toward organizational citizenship behavior. Motivation and job satisfaction have a significant influence toward organizational citizenship behavior at once. While the influence of motivation and job satisfaction toward organizational citizenship behavior is 45.8% and the rest is influenced by other variables that is not studied.